PLACE DE LA PEDAGOGIE DIFFERENCIEE POUR FAVORISER LA REUSSITE DE TOUS LES ELEVES (EXEMPLE : TRAVAIL EN GROUPE) - Attrassi, Khaled; Haimed, Mohamed (European Scientific Journal, ESJ, 2015)
Differentiated instruction is a pedagogy based on the differentiation of students’ learning process, which, to be completed, requires, on the part of the teacher, a diverse organization of educational process. Since the beginning of the school year 2013/2014, we could see significant differences between students in the same class. We wanted to think about this problem in order to ensure that all students succeed. It was therefore concluded to implement differentiated instruction to make these heterogeneities wealth. We chose to differentiate learning situation: the pedagogy of the group. After testing this method of differentiation, it seems that the group is a facilitator of learning; it can lead to greater autonomy and self-worth.